Applying ontological modeling on quranic 'nature' domain - Sadi A.B.M.S.; Anam T.; Abdirazak M.; Adnan A.H.; Khan S.Z.; Rahman M.M.; Samara G. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus